A psychoanalytical approach to management research: the psychoanalytical problem, its resolution, and derivate research method - Bocatto, Evandro; Perez-de-Toledo, Eloisa (My University, 2022)
Karl Popper has locked the reasoning of many researchers on a particular kind of rational thinking, that is, hypotheses stating and testing. For this reason, social sciences started to privilege a specific theory of personality. It is accurate to state that the common-sense knowledge, and resultant human "irrational" action, can be explained and even confronted by testing its assumptions. Nevertheless, Popper's categorization is not the only one possible. It neglects the irrationality of unconscious' intentions, a competing drive that directs human actions. In this paper, we discuss that, in accordance, management research and practice have strict relations with theories of personality that neglect the unconscious. For that reason, it assumes that humans are self-interested organisms like guinea pigs, neglecting this complementary supposition: the unconscious's intentions, structure, and dynamics that also drive human behavior, thinking, feeling, perceiving, and learning. The crucial integration of objective knowledge with the unconscious dynamic supposes the addition of the psychoanalytical problem to Popperian's psychological problem. Thus, the derivate capacity to explain human and social action understood as intention, plan, and act must consider conscious and unconscious intentions. The psychoanalytical approach to management research also provides ingenious methods like the awareness-enhancing interviews we present.
Presented on June 2-3, 2022 at the 21st European Conference on Research Methodology for Business and Management Studies (ECRM 2022) held at the University of Aveiro, Portugal.
Keywords: psychoanalysis; qualitative methodology; phenomenology; awareness-enhancing questions